Trinity and freedom: A response to Molnar - Hensley, Jeffrey (Scottish journal of theology, 2008)
Despite the renaissance of trinitarian reflection during the last half-century of Christian theology, the doctrine of the immanent Trinity – God's triune being in se as distinct from God's acts or operations ad extra – has suffered significant neglect. Following Karl Rahner's now famous axiom that ‘the “economic” Trinity is the “immanent” Trinity and the “immanent” Trinity is the “economic” Trinity’, contemporary theologians have focused primarily on the economy of salvation as the means by which God's triune being is known. Speculation about the inner life of God, abstracted from God's own self-revelation, has been eschewed for its tendency to turn the immanent Trinity into a rarified, esoteric doctrine with little influence on practical piety. Thus for most contemporary theologians, the neglect of the doctrine of the immanent Trinity is quite benign.